PENGARUH KECERDASAN ADVERSITAS, PENDIDIKAN KEWIRAUSAHAAN DALAM KELUARGA, DUKUNGAN KELUARGA, DAN EFIKASI DIRI PADA INTENSI BERWIRAUSAHA SISWA SMK NEGERI 2 NGANJUK - Fradani, Ayis Crusma (UNIVERSITAS NEGERI SURABAYA, 2014)
This research is aimed to find out the effect of intelligence adversity, entrepreneurship education in the family, family support, and self-effication on entrepreneurship intention of the 2nd Vocational High School of Nganjuk. The sampling technique used is proportionate stratified random sampling, 194 respondents. The result with partial analysis showed that the adversity intellintelligence, entrepreneurship education in the family, family support, and self effication on entrepreneurship intention are significantly affect. The result with simultaneous analysis showed that intelligence adversity, entrepreneurship education in the family, family support and self-effication on entrepreneurship intention are significantly affect